A Study of Hematological Changes in Neonatal Sepsis - Makadia, Khushbu Dalasukhbhai; Shah, Pragnesh (Annals of Pathology and Laboratory Medicine, 2020)
Background: Neonatal sepsis is one of the major causes of morbidity and mortality in the newborn. Early diagnosis and treatment are crucial in the management of neonatal sepsis. Blood culture, the gold standard, takes long time and lack sensitivity. Hematological sepsis score is a simple score obtained by combining routinely available tests and is rapid, non-expensive and has shown good correlation with blood culture. With this background the study was carried out to evaluate hematological changes in neonatal sepsis and to analyse the diagnostic utility of hematological scoring system (HSS) and its correlation with C- reactive protein and blood culture in neonatal sepsis. Methods: The study included 200 neonates admitted to Neonatal Intensive Care Unit with clinical suspicion of neonatal sepsis. CBC, Peripheral blood smear, CRP and Blood culture were obtained from all the neonate. Hematological sepsis score was calculated, and its sensitivity and specificity were obtain using blood culture as gold standard. Result: We screened 200 neonates with suspected neonatal sepsis. Blood culture was positive in 101 (50.5%) and HSS score >2 was found in 80 (40%) neonates. CRP and HSS had sensitivity of 84.15% and 72.27% and specificity of 68.68% and 92.92% respectively. Conclusion: Our study shows that HSS had fairly good sensitivity and specificity for neonatal sepsis screening and HHS can be utilized for neonatal sepsis screening.